The Fertilization of Synbiotic Systems in the Intensive Culture of Penaeus vannamei - Otávio Augusto Lacerda Ferreira Pimentel; Wilson Wasielesky; Luis Otavio Brito; Luke Aaron Roy; Nicholas Romano; Dariano Krummenauer (Reviews in Aquaculture, 2025)
Over the years, the intensification of shrimp Penaeus vannamei production has brought challenges such as disease outbreaks and increases in the nutrient loading of effluents. To be more environmentally friendly as production systems intensified, it became necessary to create systems with a high degree of biosecurity and toward efficiency in water and land use. Thus, microbial‐based systems, such as the biofloc, were pioneered to support industry growth and market demand for shrimp. Currently, a derivation of biofloc has emerged and is gaining ground in the shrimp industry, which is the synbiotic system. Synbiotic systems are microbially based and are characterized by fertilizing the culture water with vegetable bran (prebiotics) that were processed by fermentation and/or microbial respiration by probiotic microorganisms. The fertilization strategy creates conditions similar to a natural environment by supporting microbial loop development, controlling water quality, and suppressing harmful, and pathogenic microorganisms. The synbiotic system is still new and without standard fertilization protocols, which has leads to dissimilar results between laboratory research and commercial farms. Therefore, this review is focused on describing the different fertilization procedures used in the synbiotic system for P. vannamei intensive culture, the importance of each fertilizer component, as well as the processing strategies. Furthermore, in this study, we seek to demonstrate perspectives and recommend future research topics to better understand the advantages and disadvantages of this production system.